Logit Model for Sovereign Credit Ratings in South Africa (Acta Universitatis Danubius. Œconomica, 2024)
The transition of Bretton-Hoods Institutions from being providers of concessionary funding into brokers of private capital implies that credit ratings have become the lynch pin to capital access. The study critically investigates whether the determinants of credit ratings identified in literature are relevant to South Africa. Single country studies that identify the drivers of rating scores in South Africa are scant. Fitch and Standard and Poor ratings are collected for the 22 years ending 2022.  Binary framework econometric approach with the use of logit regression methods was adopted. Given the binary nature of the dependent variable, a non-linear formulation that forces the predicted values to be between 0 and 1 is desirable.  Across the two international credit ratings, the explanatory power of the estimated models has good performance. Evidence is provided in the study that six macroeconomic variables drives credit ratings in South Africa. The variables are the balance of payment, current account balance, inflation, ratio of foreign debt to GDP, gross domestic product, and the ratio of house-hold debt to disposable income. The exchange is not an essential determinant of sovereign ratings in South Africa. Based on the empirical findings of the study, it is recommended that the government of South Africa should implement polices that stabilises macroeconomic fundamentals. Structural production bottlenecks need urgent attention to enhance the investment attractiveness of the country and boost GDP. Furthermore, the study recommends that the government institute measure to stabilise debt levels at both national and household level.